The association between the quality and quantity of carbohydrate intake and the size, depth, and Wagner grade of diabetic foot ulcers in patients with type 2 diabetes. - Faezeh Geravand; Ensieh Nasli-Esfahani; Mohsen Montazer; Moharam Jalalzadeh; Leila Azadbakht (PLoS ONE)
Aims This cross-sectional study aimed to investigate the association between carbohydrate quantity and quality and the size, depth, and Wagner grade of diabetic foot ulcers (DFUs). Methods The study was conducted on 300 participants with DFUs at the Diabetes Clinic of Tehran University of Medical Sciences. Dietary intake was assessed using three 24-hour dietary recalls. Anthropometric measurements, physical activity levels, and socioeconomic factors were evaluated. The location, Wagner grade, length, width, and depth of the diabetic foot ulcer, were assessed by reviewing the patient's medical records and utilizing the information recorded therein. Results The findings indicated that out of all the carbohydrate indices examined, only the ratio of whole grain to total grain intake had a significant association with the length of the diabetic foot ulcer. Specifically, participants who consumed lower amounts of whole grain had larger diabetic foot ulcers compared to those with higher whole grain intake (0.85 Vs 0.54, Pvalue = 0.04). This relationship remained significant even after adjusting for potential confounding factors such as age, gender, total energy intake, smoking, physical activity, good shoe condition, and BMI (0.71 Vs 0.52, Pvalue = 0.03). Conclusion The findings emphasize the significant role of whole grain intake in the healing process of DFUs. However, further research with larger sample sizes is needed to investigate the impact of other carbohydrate indices.